Bounded in the mean solutions of a second-order difference equation - Mykhailo Horodnii (VTeX, 2021)
Sufficient conditions are given for the existence of a unique bounded in the mean solution to a second-order difference equation with jumps of operator coefficients in a Banach space. The question of the proximity of this solution to the stationary solution of the corresponding difference equation with constant operator coefficients is studied.